ANALYSIS THE RELATIONSHIP OF CUSTOMER PROTECTION TO THE CUSTOMER SATISFACTION IN AXA FINANCE INSURANCE MANADO - Sondakh, Aristide G. S.; Worang, Frederik G.; Pandowo, Merinda (Universitas Sam Ratulangi, 2017)
Abstract: Some of the regulation might have impact to the customer’s satisfactions, While, rules that have been determined by the government asked the right of consumers could be fulfilled, based on the obligation which should be done by consumers. On the relationship between line with the act no.8 of 1999 on consumer protection and customer satisfaction, can be known that consumer protection is instrument pivotal to the ethics business. Consumer protection is Laws to protect people when they have bought goods or services, covering things such as price, quality, or safety. The aim for this study is to analysis of act no.8 of 1999 about the customer protection in AXA Finance Insurance Manado. The population of this research is the Customer who has been joined for AXA Health Insurance for more than 3 years and active until now. The sample of this research using purposive sampling with qualitative methodology of the sample is little and selected according to the purpose of research. Keywords: customer protection, customer satisfaction, insurance